Asymmetric distribution of reconnection jet fronts in the Jovian nightside magnetosphere. Issue 1 (31st January 2013) - Kasahara, S.; Kronberg, E. A.; Kimura, T.; Tao, C.; Badman, S. V.; Masters, A.; Retinò, A.; Krupp, N.; Fujimoto, M.
Abstract : Magnetic reconnection plays important roles in mass transport and energy conversion in planetary magnetospheres. It is considered that transient reconnection causes localized auroral arcs or spots in the Jovian magnetosphere, by analogy to the case in the Earth's magnetosphere. However, the local structures of transient reconnection events (i.e., magnetospheric plasma parameters) and their spatial distribution have not been extensively investigated for the Jovian magnetosphere. Here we examine plasma velocity and density during strong north‐south magnetic field events in the Jovian nightside magnetosphere, which may be associated with tail reconnection. We find prominent reconnection jet fronts predominantly on the dawnside of the nightside magnetosphere, which would be a signature unique to rotation‐dominant planetary magnetospheres. The observed plasma structures are consistent with significant field‐aligned currents which would generate localized aurora. Key Points: Strong north‐south magnetic field events in the Jovian tail are examined Prominent jet fronts are identified predominantly on the dawnside Significant density drop indicates lobe reconnection on the dawnside